PENGARUH PENGETAHUAN, PELAYANAN, BIAYA KEPATUHAN, DAN SANKSI PADA KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK HOTEL - Sucahyani, Arum; Sukartha, I Made (E-Jurnal Akuntansi; Vol 20 No 1 (2017), 2017)
Taxpayer  Compliance is a condition where the taxpayer meets all obligations and obtain taxation rights in accordance with applicable law. This study aims to determine the effect of tax knowledge, service tax authorities, tax compliance costs and tax penalties on tax compliance in paying taxes hotels in Tabanan District Revenue Service. Methods of data collection in this study using a questionnaire survey instruments. The samples used are 120 taxpayer hotels is calculated using the formula slovin the sampling method used is the method of random sampling. The data analysis technique used is multiple linear regression analysis. According to the research, this study shows that the variable tax knowledge, service tax authorities and tax penalties positive effect on tax compliance in paying taxes hotels in Tabanan District Revenue Services, while variable tax compliance costs have negative effects on tax compliance in paying taxes hotels in Tabanan District Revenue Services.
Keywords: obedience, Knowledge, Services, Cost, Penalties